2007
DOI: 10.1086/521069
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Dust in Primeval Galaxies: A Simple Physical Model for Lyman Break Galaxies and Lyα Emitters

Abstract: We explore the onset of star formation in the early universe, exploiting the observations of high-redshift LBGs and Ly emitters (LAEs), in the framework of the galaxy formation scenario elaborated by Granato and coworkers, already successfully tested against the wealth of data on later evolutionary stages. Complementing the model with a simple, physically plausible recipe for the evolution of dust attenuation in metal-poor galaxies, we reproduce the LFs of LBGs and of LAEs at different redshifts. This recipe y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(146 citation statements)
references
References 103 publications
(153 reference statements)
7
138
1
Order By: Relevance
“…This is at variance with other models which put a strong limitation on the maximum age of Lyα emitting galaxies (e.g. Mao et al 2007;Mori & Umemura 2006). Therefore our result that LBG L and LBG N have very similar ages and the fact that we do find Lyα emitting galaxies with ages exceeding several hundred Myrs also nicely agrees with the Verhamme et al model.…”
Section: A Simple Scenariosupporting
confidence: 86%
“…This is at variance with other models which put a strong limitation on the maximum age of Lyα emitting galaxies (e.g. Mao et al 2007;Mori & Umemura 2006). Therefore our result that LBG L and LBG N have very similar ages and the fact that we do find Lyα emitting galaxies with ages exceeding several hundred Myrs also nicely agrees with the Verhamme et al model.…”
Section: A Simple Scenariosupporting
confidence: 86%
“…Finally, we note that other models that predict the evolution of the LF of high-z LAEs are available in the literature (Baugh et al 2005;Le Delliou et al 2006;Cole et al 2000;Mao et al 2007; Thommes & Meisenheimer 2005;Mesinger & Furlanetto 2008), see also Nilsson et al (2007) for a comparison of some of these models. These models add various ingredients into the simulations, and discussing our results in the light of each of these models is beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…For example most authors that have modeled the Lyα population to reproduce the LF and clustering properties of LAEs and of LBGs (e.g. Mao et al 2007 Recently Finkelstein et al (2008b) found 2 out of 15 LAEs to be consistent with evolved galaxies with ages around 0.5 Gyr, with the rest confined to ages below few tens of Myr. They suggested a possible bi-modality in the age distribution of LAEs.…”
Section: Discussionmentioning
confidence: 99%